Predicting positive and negative change in expeditioners at 2-months and 12-months post Antarctic employment - Moult, C (2014)
Extreme weather conditions and geographical isolation are among many factors that render Antarctica a challenging environment for employees to sustain optimum levels of functioning. However, challenges associated with Antarctic employment can extend beyond their time “on the ice” to influence post-Antarctic adjustment. The current study investigated predictors of positive and negative psychological change reported by expeditioners 2 and 12 months post-return from “the ice” to identify factors that influence adjustment following Antarctic employment. The sample comprised 383 (277 male, 106 female) expeditioners, recruited from Australian Antarctic program between years 2005 and 2010. Scores on the Changes in Outlook Questionnaire (CiOQ) were examined at 2 and 12 months post-return. Results indicated that positive and negative psychological change at both time points was predicted by pre-departure and post-return factors, not by experiences whilst “on the ice”. It was also identified that predictors of positive and negative change differed as a function of relationship status. This indicates that expeditioners would benefit from proactive prevention and intervention strategies prior to departure and upon return from their employment, not simply whilst working in Antarctica. Additionally, the nature of such interventions needs to consider relationship status as a factor that can influence post-return adaptation and functioning.